Design and Development of a Web-Based Financial Reporting Application for UD Jaya Abadi, Magetan - Handika Asep Kurniawan; Ardila Prihadyatama; Sasmito Widi Nugroho; Dhea Dwi Kurniawati (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
In the digital era, business entities increasingly rely on computerized systems to manage financial activities efficiently. This study aims to design and develop a web-based financial reporting application for UD Jaya Abadi, a trading company located in Magetan Regency. The development process utilized the Rapid Application Development (RAD) methodology to ensure user involvement and rapid prototyping. Data were collected through observation and interviews with the business owner to identify problems in manual bookkeeping and report preparation. The resulting application automates financial processes including sales, purchases, journal entries, and financial reporting in accordance with SAK ETAP standards. System modules include master data management, transaction recording, and financial reporting such as income statements, balance sheets, and cash flow reports. Testing using the black box method confirmed that all system functions operated correctly. This web-based system enhances data accuracy, minimizes human error, and provides real-time access to financial information, significantly improving the efficiency of financial management at UD Jaya Abadi.